Targeting CDCP1 boost CD8+ T cells-mediated cytotoxicity in cervical cancer via the JAK/STAT signaling pathway - Jie Li; Wei Wang; Chunyu Zhang; Tianyu Liu; Li Yuan; Yili Chen; Qiqiao Du; Junxiu Liu; Jiaming Huang; Yanchun Liang; Shuzhong Yao; Hua Huang; et al. (Journal for ImmunoTherapy of Cancer)
Background Cervical cancer remains a global health challenge. The identification of new immunotherapeutic targets may provide a promising platform for advancing cervical cancer treatment.Objective This study aims to investigate the role of CUB domain-containing protein 1 (CDCP1) in cervical cancer progression and evaluate its potential as a therapeutic target.Methods We performed comprehensive analyses using patient cohorts and preclinical models to examine the association between CDCP1 expression and cervical cancer prognosis. Then in immunodeficient and immunocompetent mouse models, we further investigated the impact of CDCP1 on the tumor immune microenvironment, focusing on its effects on tumor-infiltrating T cells, including cytotoxic T lymphocytes (CTLs) and regulatory T cells (Tregs). Mechanistic studies were performed to elucidate the pathways involved in CDCP1-mediated immune modulation, in particular its interaction with the T cell receptor CD6 and the activation of the JAK-STAT signaling pathway.Results Our results show that CDCP1 overexpression is associated with poor prognosis and T cell infliction in cervical cancer. Specifically, it affects the activity of CTLs and Tregs. Mechanistically, CDCP1 binds to CD6 and inhibits the JAK-STAT pathway of T cells. The study further demonstrates that targeting CDCP1 with the inhibitor 8-prenylnaringenin (8PN) effectively suppresses tumor growth in vivo and enhances antitumor immunity.Conclusions CDCP1 plays a critical role in cervical cancer progression by modulating the tumor immune microenvironment. Targeting CDCP1 offers a promising therapeutic strategy to improve the outcome of patients with cervical cancer.